BLOCK SEQUENCING ANALYSIS AND IMPORTANCE OF MINING RECOVERY AND DILUTION IN MINE PLANNING - Alimzhanov, Akseleu (Nazarbayev University School of Mining and Geosciences, 2022)
A critical step in open pit mining is determining the appropriate sequence of block extraction, which has a significant impact on mining profitability. The open-pit mining block sequencing issue, which emerges at this stage, is described to find the optimal sequence in which blocks should be extracted following numerous physical and technological restrictions. Moreover, mine planning should take mining recovery and dilution into account and engage fully in planning and optimization processes. The optimal mining block sequencing provides the highest net present value (NPV) of the project. This paper proposes a mathematical model and software computation for the open-pit mine block sequencing in open pit mining operations. The primary goal was to analyze sequencing, the ultimate pit limit, pushbacks, and scheduling simulation findings, which correspond to real-world mining projects in Datamine Studio NPVS, and compare with optimistic and pessimistic scenarios. The results showed the highest Net present value is observed in Pit no. 88 in the optimistic scenario (+20% in price) – 914,612,423 $, while the lowest NPV results were in the pessimistic scenario (-20% in price) - 356,593,171 $ in Pit no. 82 Moreover, possible optimization improvements of block sequencing, ore recovery and dilution will be addressed. To demonstrate the superior attributes of the enhanced model, an open-pit gold mine case study was presented. The combination of direct block sequencing and the traditional method allows for improving NPV results by 0.43% which is regarded as an achievable outcome. Mine planning software must develop and adapt to meet current requirements and improve innovative solutions to existing block sequencing problems.
Keywords: Type of access: Open Access